ANALISIS LUNTURNYA MORAL BANGSA DALAM PERSPEKTIF PENDIDIKAN BUDI PEKERTI KI HADJAR DEWANTARA - Dadang Mulyana; Cahyono Cahyono; Sri Wahyuni Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to determine the concept of fading Moral of the Nation in the Educational Perspective of Ki Hadjar Dewantara's Character Education. This research is motivated by the fading of the nation's moral values ​​in society, including: many cases or actions that deviate from moral values which leads to moral decline. Many moral rules often violated because it is considered old-fashioned and outdated, especially in the eyes of today's youth. Moral and virtuous character itself is a standard of good and bad for individuals in it there are moral, social, and cultural values ​​as social members. Ki Hadjar Dewantara stated that character education supports growth and development of children's lives physically and mentally. This research uses the method qualitative research with a phenomenological study design that took place in Kampung Kosambi, Cibodas Village, Lembang District, West Bandung Regency. Source The data used are primary and secondary data sources. Technique data collection using observation, interviews, and documentation. The data obtained and collected are then analyzed analysis with data reduction techniques, data presentation, drawing conclusions and verification. This research can be concluded that the factors that cause moral decline in the perspective of character education Ki Hadjar Derwantara is the parenting style of parents, the community, friends, and the times.